Presentation: Bundles of Joy? Using the ERA database to explore the outcomes of CSA practice interactions - Steward, Peter R.; Lamanna, Christine; Rosenstock, Todd S. (2019)
Bundles of Joy? Using the ERA database to explore the outcomes of CSA practice interactions. Presentation at the Global Science Conference for Climate-Smart Agriculture, 8-11 October 2019, Bali, Indonesia.